PENGUATAN KAPASITAS KELOMPOK USAHA MASYARAKAT ADAT: STRENGTHENING CAPACITY OF INDIGENOUS COMMUNITY-OWNED BUSINESS GROUPS - Agustina Widi Palupiningrum; Suhendi Suhendi; Fithriyyah Shalihati (Jurnal Abdimas Bina Bangsa, 2023)
Indigenous Community-Owned Enterprises (BUMMA) and Indigenous Community Business Groups (KUMA) manage productive businesses in the fields of local food, handicrafts, agricultural and plantation products as well as the development of environmental services. BUMMA and KUMA at the regional and community levels are driven by cadres from the indigenous territory who have a passion for developing the economic potential in the Indigenous Territory into a business. The business development of BUMMA and KUMA is considered to face various challenges, both from the internal and external environment. The managers of BUMMA and KUMA have not been able to clearly identify the business model, financial management, and market development so their business management is underdeveloped. The purpose of this activity is to increase the capacity of BUMMA and KUMA managers, evaluate and strengthen business models in various businesses that are currently being occupied. The number of training participants was 14 people who were representatives of BUMMA and KUMA who were invited. The training implementation is divided into three stages, namely the introduction of business models with the Business Model Canvas (BMC) approach, business finance management and marketing. The resulting output target is that BUMMA/KUMA representatives can describe their current business model and write a list of expectations that need to be improved in the future, and evaluate their financial management and marketing. Evaluation of the activity showed that there was an increase in the participants' knowledge regarding business model elements and how to apply them, on the other hand, there was awareness regarding business financial management and marketing which must continue to be improved to support business development